Numerical Flexibility Practices in Working Relations and Their Effects on Intergenerational Solidarity Processes - Serkan Coşkun (İstanbul Üniversitesi Sosyoloji Dergisi)
This study examines the interactions between the numerical flexibility practices emerging in today’s working relations and intergenerational solidarity relations and in this context aims to describe in depth the effect these practices have on these relations. This study is structured within the framework of the phenomenological design, a qualitative research method, with data being collected using semi-structured interview forms. The study uses the program MAXQDA Pro Analytics 2020 to analyze the data and conducted three-stage thematic coding to form code co-occurrence clusters. According to the analysis results, i) numerical flexibility practices in working relationships are multidimensional in terms of how they reflect ontoindividuals and are closely related to the precariousness of work conditions, ii) flexible work hours affect individuals’ functional and associational sharing with their parents, and iii) individuals’ consensual status with their parents regarding work shapes the processes of affectual solidarity. The interaction of normative solidarity in the cultural context is seen to be a crucial factor for making sense of the solidarity process, with normative solidarity’s interaction with material resources possibly being the cause of solidarity processes taking different than expected forms.